1997
DOI: 10.1097/00004032-199707000-00017
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Prevalence of Thyroid Disease on Kwajalein Atoll, Marshall Islands

Abstract: The prevalence of thyroid nodules and thyroid cancer was studied in the indigenous population residing on Ebeye Island, Kwajalein Atoll, in the Republic of the Marshall Islands. This island, centrally located in the nation, is home to about 25% of the nation's population, many who have migrated there from other atolls. The objective of the study was to obtain thyroid disease rate statistics on as much of the population as possible that was alive during the years of nuclear testing and to test the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Marked increases in childhood thyroid cancer have since been reported for areas surrounding the Chernobyl reactor especially in Belarus and Ukraine (66)(67)(68). Pacini et al evaluated thyroid cancer cases reported from registries in Belarus since 1986 and compared them with presumably unexposed cases reported from registries in France and Italy (66).…”
Section: B2b3 Chernobylmentioning
confidence: 99%
See 1 more Smart Citation
“…Marked increases in childhood thyroid cancer have since been reported for areas surrounding the Chernobyl reactor especially in Belarus and Ukraine (66)(67)(68). Pacini et al evaluated thyroid cancer cases reported from registries in Belarus since 1986 and compared them with presumably unexposed cases reported from registries in France and Italy (66).…”
Section: B2b3 Chernobylmentioning
confidence: 99%
“…In addition, the combined effects of deviations in more than one of these assumptions were investigated. The detailed results of these sensitivity calculations were provided in the Pilot Study Final Report (pages [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Based on the results, the following conclusions were reached:…”
Section: Planmentioning
confidence: 99%
“…The medical monitoring has been described in detail elsewhere. 8,11 Three study populations (birth cohorts) were defined: those born before the BRAVO test on March 1, 1954 (Bravo cohort), those born between March 1, 1954 and the end of the bomb test period (end-of-testing cohort), and those born between March 1, 1959 and January 1, 1965 (after testing cohort), the latter group to serve as unexposed control. The end-of-testing cohort included people who were in utero for more than three months at the end of the last atomic bomb detonation in August 1958 and thus were born before March 1, 1959 since the fetal thyroid actively concentrates iodine from the fourth month of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…' We previously showed that thyroid nodules were very common, in particular in female Marshallese, and that the prevalence increased with age, but we found little evidence that benign thyroid nodules were related to exposure from nuclear fallout. [8][9][10][11] In 2001, we published a monograph that summarized our previous findings systematically. 11 In the monograph, we reported that the occurrence of thyroid cancer in Marshallese was still high in 40 years after the nuclear test and that the association between thyroid cancer prevalence and radio-iodines exposure using the data collected until the end of 2000.…”
Section: Figure Map Of the Marshall Islandsmentioning
confidence: 99%
“…Tumor development reaches a peak in 25-29 y. They have also been reported to develop as much as 40 -45 y later (Kasatkina et al 1997;Nikiforov and Fagin 1997;Schneider et al 1993;Hamilton et al 1987;Takahashi et al 1997;Cotterill et al 2001). Humans are subjected to radiation from external and/or internal radioactive sources.…”
Section: Introductionmentioning
confidence: 99%